Camaraderie and Identity in the Crucible of War: Analysing Gregory Burke’s Black Watch - Sedat Bay (Journal of Literature and Humanities)
This research examines how the intense experiences of war shape the bonds between soldiers and their sense of self, as portrayed in Gregory Burke's Black Watch. By thoroughly analysing the play, this study explores how shared experiences, adversity, and the allure of collective belonging shape soldiers’ identities. This study investigates how military identity develops, focusing on the impact of historical, traditional, and shared cultural elements. Moreover, it investigates the dynamic conflict concerning individual and collective identities, highlighting the pressures to conform while preserving individuality. Drawing on social identity theory, the essay explores how broader social constructs intersect with military experiences, shaping soldiers’ perceptions and behaviours. Ultimately, this study aims to enhance the comprehension of the psychological and social intricacies experienced by service members, illuminating the lasting effects of war on both individuals and society.